Sulla cristologia pneumatica: Tensioni interpretative e guadagni derivati - Brambilla, Paolo 1979- (2025)
The article analyses some tensions in Christology that are closely related to pneumatology. Three areas are examined: the history of Jesus as the site of his "becoming" the Son of God; the interpretation of ancient Christology between Spirit and Logos Christology; the anointing of Christ in the Spirit at the Jordan. In each of these three areas the presence of polarities is emphasized. These polarities are found in Scripture, appear in the Fathers and reappear in various ways in contemporary theology. The conclusions stress the need to maintain certain hermeneutical tensions in contemplating the mystery of Christ in order to avoid simplification.